Efficacy and safety of nintedanib in a Greek multicentre idiopathic pulmonary fibrosis registry: a retrospective, observational, cohort study. Issue 1 (27th January 2020) - Antoniou, Katerina; Markopoulou, Katerina; Tzouvelekis, Argyrios; Trachalaki, Athina; Vasarmidi, Eirini; Organtzis, Jiannis; Tzilas, Vasilios; Bouros, Evangelos; Kounti, Georgia; Rampiadou, Christina; Kotoulas, Serafeim-Chrysovalantis; Bardaka, Fotini; et al.
Nintedanib is a tyrosine kinase inhibitor approved for the treatment of idiopathic pulmonary fibrosis (IPF). In a retrospective, real-world study across seven Greek hospitals, we evaluated the effectiveness and safety of nintedanib in routine clinical practice. Patients diagnosed with IPF, as per guideline criteria or multidisciplinary diagnosis, received nintedanib between January 2013 and January 2018. We evaluated 244 patients: mean±sd age 71.8±7.5 years, 79.1% male, 45.1% current smokers and 33.1% ex-smokers at treatment initiation. At baseline, predicted forced vital capacity (FVC) was 73.3±20.7% and predicted diffusing capacity of the lungs for carbon monoxide ( D LCO ) was 42.6±16.7%. On average, patients spent 23.6±15.0 months on nintedanib. At 3 years, 78 patients had died, equating to a 3-year survival rate of 59.4% (unaffected by treatment discontinuation or dose reduction). FVC% pred and D LCO % pred were largely stable at 3 years, with no significant difference from baseline (FVC 73.3±20.7% pred versus 78±20.1% pred, p=0.074; D LCO 42.6±16.7% pred versus 40.4±18.1% pred, p=0.334). Of the 244 patients, 55.7% reported an adverse event. Gastrointestinal events were the most common (173 (77.2%) out of 224 total events) and 45.0% of patients experienced diarrhoea. Only 32 (13.1%) patients had to permanently discontinue nintedanib due to an adverse event. This real-world study shows a 3-year survival rate of 59.4% and a low discontinuation rate due to adverse events. Our experience is consistent with previous findings in clinical trials of nintedanib in IPF. Findings from the largest registry of Greek patients with IPF receiving nintedanib in routine clinical practice show, over a 3-year period, a low discontinuation rate and efficacy data that support the results of the INPULSIS clinical trials http://bit.ly/35a2CS5